Seroprevalence of Toxoplasma gondii in domestic pigs, sheep, cattle, wild boars, and moose in the Nordic-Baltic region: A systematic review and meta-analysis. (May 2019) - Olsen, Abbey; Berg, Rebecca; Tagel, Maarja; Must, Kärt; Deksne, Gunita; Enemark, Heidi Larsen; Alban, Lis; Johansen, Maria Vang; Nielsen, Henrik Vedel; Sandberg, Marianne; Lundén, Anna; Stensvold, Christen Rune; et al.
Abstract: Background: Toxoplasma gondii is an important foodborne zoonotic parasite. Meat of infected animals is presumed to constitute a major source of human infection and may be a driver of geographical variation in the prevalence of anti- T. gondii antibodies in humans, which is substantial in the Nordic-Baltic region in northern Europe. However, data on seroprevalence of T. gondii in different animal species used for human consumption are scattered. Methods: We conducted a systematic review of seroprevalence studies and meta-analysis to estimate the seroprevalence of T. gondii in five animal species that are raised or hunted for human consumption in the Nordic-Baltic region: domestic pigs ( Sus scrofa domesticus ), sheep ( Ovis aries ), cattle ( Bos taurus ), wild boars ( Sus scrofa ), and moose ( Alces alces ). We searched for studies that were conducted between January 1990 and June 2018, and reported in articles, theses, conference abstracts and proceedings, and manuscripts. Subgroup analyses were performed to identify variables influencing the seroprevalence. Findings: From a total of 271 studies identified in the systematic review, 32 were included in the meta-analysis. These comprised of 13 studies on domestic pigs, six on sheep, three on cattle, six on wild boars, and four on moose. The estimated pooled seroprevalence of T. gondii was 6% in domestic pigs (CI95% : 3–10%), 23% in sheep (CI95% : 12–36%), 7% in cattle (CI95% : 1–21%), 33% in wild boars (CI95% : 26–41%), and 16% in moose (CI95% : 10–23%). High heterogeneity was observed in the seroprevalence data within each species. In all host species except wild boars, the pooled seroprevalence estimates were significantly higher in animals >1 year of age than in younger animals. Not all studies provided information on animal age, sensitivity and specificity of the serological method employed, and the cut-off values used for defining an animal seropositive. Conclusions: A substantial proportion of animals raised or hunted for human consumption in the region had tested positive for T. gondii . This indicates widespread exposure to T. gondii among animals raised or hunted for human consumption in the region. Large variations were observed in the seroprevalence estimates between the studies in the region; however, studies were too few to identify spatial patterns at country-level.